Undergraduate Students’ Views on the Use of Online Learning Platform during COVID-19 Pandemic - Fatimah Mulya Sari; Lulud Oktaviani (TEKNOSASTIK, 2021)
Technology-based online learning platforms have supported and helped Indonesian students to succeed the online learning education amid the novel coronavirus. They are allowed to access learning materials, learning activities, and learning practice for free. The purpose of this paper is to investigate the students’ paradigms on how effective is online learning platforms for their learning process. A qualitative method in form of a case study design was applied to this present study which had a hundred and eighty-five undergraduate students as the subjects. A questionnaire consisting of twenty-five statements was distributed to them through Google Forms. A follow-up interview via WhatsApp video calls was also conducted with the forty students who were chosen randomly to strengthen the findings. The results of this study show that most students agreed that the online learning platform might provide some beneficial effects for them. They mentioned that online activities through this platform were easily followed and challenge them to strive for keeping their balance motivation and interest to accomplish the online learning process. They were comfortable communicating and interacting with classmates and lecturers electronically. Besides, they might also be able to manage their study time and self-disciplined. Therefore, an online learning platform is considered to be a beneficial tool to support online learning environments.